Total phenolic and flavonoid content and antibacterial activity of Punica granatum L. var. pleniflora flowers (Golnar) against bacterial strains causing foodborne diseases. Issue 1 (December 2015) - Mahboubi, Arash; Asgarpanah, Jinous; Sadaghiyani, Parisa; Faizi, Mehrdad
Abstract Background Flowers ofPunica granatum L. (Punicaceae) var.pleniflora, known as "Golnar" in Iranian traditional medicine have been used for the prevention and treatment of foodborne diseases. In this study, antibacterial activities of ethanol extract of Golnar and its fractions were scientifically evaluated against bacteria causing foodborne diseases includingStaphylococcus aureus, Bacillus cereus, Listeria monocytogenes, Escherichia coli, Shigella dysantriae, andSalmonella typhi. The total phenolic and flavonoid contents of the extract and its fractions were also determined. Methods The antibacterial effect of the ethanol extract and its fractions were primarily evaluated by agar well diffusion and their MIC and MBC were determined by broth macro dilution method. The total phenolic and flavonoid contents of the extract and its fractions were measured based on gallic acid and rutin equivalents (GAE and RE), respectively. Results After evaluation of total phenolic and flavonoid content the chloroform fraction showed the lowest phenolic and flavonoid contents (3.8 mg GAE/g and 1.1 mg RE/g respectively) and the methanol fraction showed the highest phenolic and flavonoid contents (18.1 mg GEA/g and 3.3 mg RE/g respectively). The total phenolic and flavonoid content was positively associated with the antibacterial activities of the fractions with chloroform extract exhibiting lowest antibacterial activity againstE. coli (MIC 25 mg/ml) and the methanol fraction exhibiting the highest antibacterial effect againstS. aureus (MIC 0.19 mg/ml). Conclusion Golnar extract showed antibacterial activity against both Gram positive and Gram negative bacteria causing food poisoning. Therefore, the extract can be used for prevention or treatment of foodborne diseases or as preservative in the food industry. The methanol fraction with the highest phenolic and flavonoid content showed the highest antibacterial effect. This indicates that the phenolic and flavonoid compounds in the extract can be responsible for the effect.